2009
DOI: 10.1165/rcmb.2008-0359oc
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Surfactant Surface Tension Influences Alveolar Capillary Shape and Oxygenation

Abstract: Alveolar capillaries are located in close proximity to the alveolar epithelium and beneath the surfactant film. We hypothesized that the shape of alveolar capillaries and accompanying oxygenation are influenced by surfactant surface tension in the alveolus. To prove our hypothesis, surfactant surface tension was regulated by conditional expression of surfactant protein (SP)-B in Sftpb 2/2 mice, thereby inhibiting surface tension-lowering properties of surfactant in vivo within 24 hours after depletion of Sftpb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…These values are comparable with %SpO 2 values reported for normoxic mouse (30). Previous studies have shown that %SpO 2 is a valid predictor of %hemoglobin oxygen saturation (%HbO 2 ) as it shows high correlation with %HbO 2 (3,40,45).…”
Section: Arterial Hemoglobin Oxygen Saturation (%Spo 2 )supporting
confidence: 88%
“…These values are comparable with %SpO 2 values reported for normoxic mouse (30). Previous studies have shown that %SpO 2 is a valid predictor of %hemoglobin oxygen saturation (%HbO 2 ) as it shows high correlation with %HbO 2 (3,40,45).…”
Section: Arterial Hemoglobin Oxygen Saturation (%Spo 2 )supporting
confidence: 88%
“…In agreement with our findings, the researchers also described “uncoupling” between sustained improved oxygenation and lung mechanics in lucinactant-treated animals. They suggested that the uncoupling is due to the presence of SP-B or SP-B-mimicking peptide, KL4, in the surfactants, which support alveolar capillary shape by reducing surface tension, thereby improving pulmonary blood flow and shunt 35. Our study showed uncoupling between C dyn and oxygenation and calculated intrapulmonary shunt, favoring the Synsurf-treated animals over that of Curosurf®- and saline-treated lambs.…”
Section: Discussionmentioning
confidence: 54%
“…Phosphorus in extracted lipid from BALF and lung homogenate was analyzed (17) for total phospholipid. Surfactant proteins (SP) in BALF containing 50 g of protein was quantified by Western blot analyses using rabbit anti-bovine SP-A, SP-B, and SP-C (Chemicon International, Temecula, CA) and normalized to ␤-actin in the sample (25). The right upper lobe was inflation-fixed at 30 cmH 2O for morphology.…”
Section: Methodsmentioning
confidence: 99%
“…Low surface tension is critical for gas exchange, alveolar capillary blood flow (25), and alveolar macrophage function of phagocytosis (1). In the fetal lung, the synthesis of pulmonary surfactant dramatically increases at late gestation to prepare for transition to air breathing at birth.…”
mentioning
confidence: 99%